A Cys2His2 Zinc Finger Transcription Factor BpSZA1 Positively Modulates Salt Stress in Betula platyphylla - Zhang, Xi; Guo, Qing; Qin, Linlin; Li, Li (Frontiers in Plant Science, 2022)
Zinc finger proteins (ZFPs) are widely involved in plant growth and abiotic stress responses, however, few of these proteins have been functionally characterized in tree species. In this study, we cloned and characterized the BpSZA1 gene encoding a C2H2-type ZFP from Betula platyphylla. BpSZA1 is a transcription factor localized in the nucleus, with a transcription activation domain located at the N-terminus. BpSZA1 was predominantly expressed in stems and was induced by salt. We generated transgenic birch lines displaying overexpression (OE) or RNAi silencing (Ri) of BpSZA1 and exposed these along with wild-type birch seedlings to salinity. Phenotypic and physiological parameters such as superoxide dismutase, peroxisome, H2O2 content, proline content, water loss rate, and malondialdehyde content were examined. Overexpression of BpSZA1 in birch conferred increased salt tolerance. Chromatin immunoprecipitation-qPCR and RNA-seq showed that BpSZA1 binds to the GAGA-motif in the promoter of downstream target genes including BpAPX1, BpAPX2, BpCAT, and Bp6PGDH to activate their transcription. BpSZA1 also participates in abscisic acid (ABA) biosynthesis, proline biosynthesis, and the ABA/jasmonic acid pathway to enhance the salt stress of B. platyphylla.